Zum Paradigma der Konfessionalisierung - Moritz, Tilman; Kopp, Stefan; Priesching, Nicole (Katholische Konfessionalisierung in Paderborn? Religiöse Prozesse in der Frühen Neuzeit)

A. Seidler, I. Monok (Hgg.): Reformation und Bücher. Zentren der Ideen – Zentren der Buchproduktion. Wiesbaden 2020 - Moritz, Tilman (sehepunkte)

Das Commentariolum Ferdinands von Fürstenberg – eine lateinisch-deutsche Synopse - Moritz, Tilman (Katholische Konfessionalisierung in Paderborn? Religiöse Prozesse in der Frühen Neuzeit)

Katholische Konfessionalisierung in Paderborn? Religiöse Prozesse in der Frühen Neuzeit

Max Schulze vs. Joana Dahlhoff - Schulze, Max (Joana Dahlhoff: Recherche patiente)

Shared Leadership: Neue Studien für die Unternehmenspraxis - Krebs, Benjamin; Kabst, Rüdiger (PERSONALquartely)

HR-Manager als Intrapreneure - Wach, Bernhard; Krebs, Benjamin; Kabst, Rüdiger (HR-Trends 2021)

Contrastive Predictive Coding Supported Factorized Variational Autoencoder for Unsupervised Learning of Disentangled Speech Representations - Ebbers, Janek; Kuhlmann, Michael; Cord-Landwehr, Tobias; Haeb-Umbach, Reinhold (Proceedings of the IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))
In this work we address disentanglement of style and content in speech signals. We propose a fully convolutional variational autoencoder employing two encoders: a content encoder and a style encoder. To foster disentanglement, we propose adversarial contrastive predictive coding. This new disentanglement method does neither need parallel data nor any supervision. We show that the proposed technique is capable of separating speaker and content traits into the two different representations and show competitive speaker-content disentanglement performance compared to other unsupervised approaches. We further demonstrate an increased robustness of the content representation against a train-test mismatch compared to spectral features, when used for phone recognition.

Human Factors in Secure Software Development - Acar, Yasemin

A Large-Scale Interview Study on Information Security in and Attacks against Small and Medium-sized Enterprises - Huaman, Nicolas; von Skarczinski, Bennet; Stransky, Christian; Wermke, Dominik; Acar, Yasemin; Dreißigacker, Arne; Fahl, Sascha (30th USENIX Security Symposium, USENIX Security 2021, August 11-13, 2021)

Why Eve and Mallory Still Love Android: Revisiting TLS (In)Security in Android Applications - Oltrogge, Marten; Huaman, Nicolas; Amft, Sabrina; Acar, Yasemin; Backes, Michael; Fahl, Sascha (30th USENIX Security Symposium, USENIX Security 2021, August 11-13, 2021)

Passivität als Widerstand gegen die Macht der Verhältnisse? Melvilles Bartleby, the scrivener aus literaturwissenschaftlicher und ökonomischer Perspektive - Öhlschläger, Claudia; Schneider, Martin (Komparatistik heute)

Happy clappy heile Welt? Wie angesichts von Krisen und Katastrophen eine schöne Welt besungen werden kann - Neumann, Anna (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr)

This is my Fight Song - Neumann, Anna; Katharina, Kammeyer; Vera, Uppenkamp (Musk als Lebensmittel)

Keller, Raabe, Fontane: ›nichts für den Durchschnittsleser‹. Miszellane Lektüren, ›imaginäre Leser‹ und Kanonisierungsprozesse in der Literaturkritik der zeitgenössischen Presse - Gretz, Daniela (Miszellanes Lesen. Interferenzen zwischen medialen Formaten, Romanstrukturen und Lektürepraktiken im 19. Jahrhundert)

Miszellanes Lesen. Interferenzen zwischen medialen Formaten, Romanstrukturen und Lektürepraktiken im 19. Jahrhundert

Mit Aufgaben im inklusiven Mathematikunterricht professionell umgehen - Erkenntnisse einer Interviewstudie mit Lehrpersonen der Sekundarstufe - Häsel-Weide, Uta; Seitz, Simone; Wallner, Melina; Wilke, Yannik; Heckmann, Lara (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)

Conceptualiziation processes of 6th graders for rotational symmetry - Hattermann, Mathias; Häsel-Weide, Uta; Wallner, Melina (Proceedings of the 44th Conference of the International Group for the Psychology of Mathematics Education)

Zusammenhang zwischen familiären Lebenssituationen und Werteähnlichkeiten in der Eltern-Kind-Beziehung im Erwachsenenalter. - Hoellger, Christian; Sommer, Sabrina; Buhl, Heike M. (Zeitschrift für Soziologie der Erziehung und Sozialisation)

Bifurcation preserving discretisations of optimal control problems - Offen, Christian; Ober-Blöbaum, Sina
The first order optimality conditions of optimal control problems (OCPs) can be regarded as boundary value problems for Hamiltonian systems. Variational or symplectic discretisation methods are classically known for their excellent long term behaviour. As boundary value problems are posed on intervals of fixed, moderate length, it is not immediately clear whether methods can profit from structure preservation in this context. When parameters are present, solutions can undergo bifurcations, for instance, two solutions can merge and annihilate one another as parameters are varied. We will show that generic bifurcations of an OCP are preserved under discretisation when the OCP is either directly discretised to a discrete OCP (direct method) or translated into a Hamiltonian boundary value problem using first order necessary conditions of optimality which is then solved using a symplectic integrator (indirect method). Moreover, certain bifurcations break when a non-symplectic scheme is used. The general phenomenon is illustrated on the example of a cut locus of an ellipsoid.
Keywords: optimal control; catastrophe theory; bifurcations; variational methods; symplectic integrators